2013
DOI: 10.1097/qai.0b013e3182a6b0be
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Condom and Diaphragm Nonadherence Among Women in an HIV Prevention Trial in Southern Africa

Abstract: Prevalence of recent IPV was high and associated with condom and diaphragm nonadherence during the trial. Counseling in prevention trials should proactively address IPV, for its own sake, and in product and risk-reduction counseling. Strategies to encourage men's positive involvement in product use and prevent IPV perpetration should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 30 publications
3
43
1
Order By: Relevance
“…Similar to prior research we found that consistent condom use among women was lower among those who had experienced IPV in their relationship,14 15 and higher among women who reported greater relationship power 6 15 16. Gender power inequities and IPV are structural pathways to women's HIV risk: they reduce women's ability to request male partners to use condoms 17.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to prior research we found that consistent condom use among women was lower among those who had experienced IPV in their relationship,14 15 and higher among women who reported greater relationship power 6 15 16. Gender power inequities and IPV are structural pathways to women's HIV risk: they reduce women's ability to request male partners to use condoms 17.…”
Section: Discussionsupporting
confidence: 87%
“…However, psychological and other forms of physical violence can increase risk by reducing women’s ability to protect themselves (e.g. to negotiate condom use) and more broadly control their sexual experiences (UN Trust Fund 2012; Kacanek et al 2013). Ingrained social, economic and political gender inequalities, or ‘structural violence,’ also contribute to women’s heightened HIV vulnerability (Farmer 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Described as technologies intended to empower women (Bell 2000), these formulations are designed to overcome at least some of the gendered barriers to protection, described above. While several of these trials have reported on the intersection between trial participation, product use, and participants’ gender roles, they typically examine these issues in the context of intimate partnerships (Stadler et al 2014; Kacanek et al 2013; Montgomery et al 2008, 2011). Within these findings, structural gender inequalities are often highlighted as shaping women’s lives and potentially influencing product use.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to PD analysis, samples were thawed on ice, clarified by centrifugation at 4ºC for 10 min at 2000 rpm, divided into aliquots (300 µL per tube) and stored at -80ºC until used. Jurkat-Tat-CCR5 T cells (1×10 5 ) in RPMI 1640 culture medium supplemented with 10% fetal bovine serum, 2 mM L-Glutamine, 100 U/mL penicillin and 100 µg/mL streptomycin (complete RPMI) were placed in round-bottomed 96-well tissue culture plates, and the plates centrifuged at 1500 rpm for 5 minutes. The supernatant was removed and 50 µL of neat or diluted (1:10 in normal saline) CVL sample was added to the cell pellets.…”
Section: Pharmacodynamic Assessment Of Anti-hiv Activity Of Dapivirinmentioning
confidence: 99%
“…Most new HIV infections in women are from heterosexual contact (84%) [3]. While male condoms are highly effective against HIV transmission, they are often inadequate prevention options for women as male partners may refuse their use [4][5][6]. The development of women-initiated HIV prevention options therefore remains a critical public health objective.…”
Section: Introductionmentioning
confidence: 99%